Repurposing of Cetuximab in antibody-directed chemotherapy-loaded nanoparticles in EGFR therapy-resistant pancreatic tumours. Issue 42 (18th October 2019) - McDaid, William J.; Greene, Michelle K.; Johnston, Michael C.; Pollheimer, Ellen; Smyth, Peter; McLaughlin, Kirsty; Van Schaeybroeck, Sandra; Straubinger, Robert M.; Longley, Daniel B.; Scott, Christopher J.
Abstract : The use of CTX as a targeting agent for camptothecin-loaded polymeric nanoparticles directed against KRAS mutant CTX-resistant cancer cells was investigated. CTX increased CPT internalisation into cancer cells resulting in elevated cancer cell death. Abstract : The anti-Epidermal Growth Factor Receptor (EGFR) antibody Cetuximab (CTX) has demonstrated limited anti-cancer efficacy in cells overexpressing EGFR due to activating mutations in RAS in solid tumours, such as pancreatic cancer. The utilisation of antibodies as targeting components of antibody–drug conjugates, such as trastuzumab emtansine (Kadcyla), demonstrates that antibodies may be repurposed to direct therapeutic agents to antibody-resistant cancers. Here we investigated the use of CTX as a targeting agent for camptothecin (CPT)-loaded polymeric nanoparticles (NPs) directed against KRAS mutant CTX-resistant cancer cells. CPT was encapsulated within poly(lactic- co -glycolic acid) (PLGA) NPs using the solvent evaporation method. CTX conjugation improved NP binding and delivery of CPT to CTX-resistant cancer cell lines. CTX successfully targeted CPT-loaded NPs to mutant KRAS PANC-1 tumours in vivo and reduced tumour growth. This study highlights that CTX can be repurposed as a targeting agent against CTX-resistant cancers and that antibody repositioning may be applicable to other antibodies restricted by resistance.